Effects of body condition score at initiation of the breeding season on reproductive performance and overall productivity of Bos taurus and B. indicus beef cows - Cooke, R. F.; Lamb, G. C.; Vasconcelos, J. L.M. [UNESP]; Pohler, K. G. (Elsevier, 2021)
This experiment was conducted to evaluate reproductive and productive responses of Bos indicus and B. taurus beef cows according to body condition score (BCS) at initiation of the annual breeding season. Non-pregnant, suckling multiparous cows were assigned to a fixed-time artificial insemination treatment regimen followed by natural service. Cows were classified as having a BCS < 5.0 (B. taurus, n = 158; B. indicus, n = 248) or BCS ≥ 5.0 (B. taurus, n = 173; B. indicus, n = 122). Calving rate was greater (P < 0.03) in cows with a BCS ≥ 5.0 (93.7 % and 85.1 % in B. taurus, 83.6 % and 73.3 % in B. indicus), which also calved earlier (P < 0.01) compared with cows with a BCS < 5.0. Cows with a BCS ≥ 5.0 weaned more (P ≤ 0.05) calves compared with those with a BCS < 5.0, which were older (P ≤ 0.04) and weighed more (P ≤ 0.09) at weaning (258 and 252 kg in B. taurus, 213 and 203 kg in B. indicus). Kilograms of calf weaned/cow in the breeding herd were greater (P ≤ 0.03) in cows with a BCS ≥ 5.0 compared with those with a BCS < 5.0 (221 and 200 kg in B. taurus, 159 and 129 d in B. indicus). Collectively, cows with a BCS ≥ 5.0 at initiation of the breeding season had greater reproductive and overall productivity during a cow-calf cycle, and these outcomes were observed in B. taurus and B. indicus cowherds.
Keywords: Beef cows; Body condition score; Cow-calf; Production; Reproduction